Short Bowel Syndrome: A Review of Management Options - Seetharam, Prasad (Medknow Publications, 2011)
Extensive resection of the intestinal tract frequently results in inadequate digestion and/or absorption of nutrients, a condition known as short bowel syndrome (SBS). This challenging condition demands a dedicated multidisciplinary team effort to overcome the morbidity and mortality in these patients. With advances in critical care management, more and more patients survive the immediate morbidity of massive intestinal resection to present with SBS. Several therapies, including parenteral nutrition (PN), bowel rehabilitation and surgical procedures to reconstruct bowel have been used in these patients. Novel dietary approaches, pharmacotherapy and timely surgical interventions have all added to the improved outcome in these patients. However, these treatments only partially correct the underlying problem of reduced bowel function and have limited success resulting in 30% to 50% mortality rates. However, increasing experience and encouraging results of intestinal transplantation has added a new dimension to the management of SBS. Literature available on SBS is exhaustive but inconclusive. We conducted a review of scientific literature and electronic media with search terms 'short bowel syndrome, advances in SBS and SBS’ and attempted to give a comprehensive account on this topic with emphasis on the recent advances in its management.